Pemeriksaan Soil Transmitted Helmints (STH) Pada Feses Petugas Pengangkut Sampah Di Desa Tawangsari Kabupaten Malang - Fahru Rizal Isyafa; Erni Yohani Mahtuti; Faisal Faisal (Journal of Educational Innovation and Public Health, 2023)
Soil Transmitted Helminths are parasitic worms found in tropical and subtropical countries that can cause helminthic infections in humans through contact with eggs, parasite larvae spread through the soil. Detection of STH infection is carried out by sedimentation and flotation methods. Garbage carriers are vulnerable to STH infection because they work directly with garbage and are in a sanitary environment that is not clean. The purpose of the study was to determine the results of STH examination on the feces of waste transport officers in Tawangsari Village, Malang Regency. Type of Descriptive Analytical research, conducted in July 2023. The sampling technique uses Total Sampling of a sample of 8 respondents. The results of the sedimentation method found 2 heads of Ascaris lumbricoides, respondents A1, A2 (1tail), the flotation method was not found helmints. The sedimentation method found eggs of Ascaris lumbricoides respondents A1, A7(1 grain) and A2, A3(2 eggs). The flotation method found eggs of Ascaris lumbricoides respondents A2(5eggs), A3(2eggs) and A6(1eggs). The results of the pearson correlation test show a relationship between STH infection and personal hygiene, the use of PPE is 0.875 > 0.01 with a value of r = -0.67 meaning that there is no relationship between personal hygiene and the use of PPE with STH infection means better personal hygiene, the use of PPE while working does not require STH infection, the relationship between STH infection and Environmental Sanitation of 0.000 < 0.01 with a value of r = -1 means that there is a strong relationship inversely proportional between Environmental sanitation with STH infection in waste haulers, means that the better the environmental sanitation, the lower the risk level of STH.